Validation of a multiplex reverse transcription and pre-amplification method using TaqMan® MicroRNA assays - Le Carré, Joane; Lamon, Séverine; Léger, Bertrand (Frontiers in Genetics, 2014)
Abstract Since the discovery of microRNAs (miRNAs), different approaches have been developed to label, amplify and quantify miRNAs. The TaqMan® technology, provided by Applied Biosystems, uses a stem-loop RT primer system to reverse transcribe the RNA and amplify the cDNA. This method is widely used to identify global differences between the expression of hundreds of miRNAs across comparative samples. This technique also allows the quantification of the expression of targeted miRNAs to validate observations determined by whole-genome screening or to analyze few specific miRNAs on a large number of samples. Here, we describe validation of a method published by Applied Biosystems on their web site allowing to reverse transcribe and pre-amplify multiple miRNAs and snoRNAs simultaneously. The validation of this protocol was performed on human muscle and plasma samples. Fast and cost efficient, this method achieves an easy and convenient way to screen a relatively large number of miRNAs in parallel.